(untitled) (Research, Society and Development, 2022)
Currently, crop protection has been carried out using pesticides, however, the inappropriate use and long periods of exposure to these products have caused a series of problems for the environment and human health. Biological control, more specifically using entomopathogenic fungi, appears as an effective and eco-friendly alternative to pesticides, however, these microorganisms are highly sensitive to some environmental conditions, such as temperature variation and ultraviolet light. Thus, some encapsulation methods have been developed to protect fungi against these factors. To a better understanding of these methods, in this work, we carried out a literature review addressing some encapsulation techniques for entomopathogenic fungi for their application in biological control. The materials used in encapsulation are synthetic polymers (polyurethane, polyacrylate, and polyvinyl alcohol) or natural polymers (alginate, starch, cellulose, and gelatin, among others). The material selected must form a stable, inert, and resistant protection capable of releasing the contents in time and under ideal conditions. Among the techniques for encapsulating entomopathogenic fungi, we can highlight thermal gelation, ionic gelation, spray-drying, coacervation, and LentiKats®. Encapsulations of Trichoderma harzianum by ionic gelation and of Beauveria bassiana by ionic gelation and spray-drying have already been successfully reported. Overall, encapsulation techniques protect fungi against environmental factors and increase the efficiency and viability of these microorganisms in the field.